2023
DOI: 10.15421/012310
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Echinacea purpurea and Silybum marianum seeds on the body of rats with an excessive fat diet

Abstract: The impact of excess fat and high-calorie intake on the human body is an acute problem for many economically developed countries. Modelling the effects on the health of rats of supplementing their diet with crushed seeds of Echinacea purpurea (L.) Moench and Sylibum marianum (L.) Gaertn was carried out in a laboratory experiment. In the control group of animals, body weight increased by 700 mg/day, with the addition of E. purpurea seeds – by 1394 mg/day and with the addition of S. marianum seeds – by only 155 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…In this study, we assessed the effect of various doses of calcium propionate as dietary supplement on the body of white laboratory rats fed a high-fat diet during a 20-day experiment for indicators of food and water consumption, changes in body weight and organs, blood biochemical parameters, the functional state of the nervous system and changes in gut microbiome composition. It is known that the body weight of animals and its changes under the influence of various factors are important indicators that are used in determining the toxicity of drugs and food additives Lieshchova & Brygadyrenko, 2023b). Also, in la-boratory animals, one of the important indicators that can be used to determine their well-being and health is the amount of food and water consumed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we assessed the effect of various doses of calcium propionate as dietary supplement on the body of white laboratory rats fed a high-fat diet during a 20-day experiment for indicators of food and water consumption, changes in body weight and organs, blood biochemical parameters, the functional state of the nervous system and changes in gut microbiome composition. It is known that the body weight of animals and its changes under the influence of various factors are important indicators that are used in determining the toxicity of drugs and food additives Lieshchova & Brygadyrenko, 2023b). Also, in la-boratory animals, one of the important indicators that can be used to determine their well-being and health is the amount of food and water consumed.…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning (days 1-4) and at the end (days 16-20) of the experiment, the functional state of the nervous system was determined by indicators of orientation-physical activity and the emotional state of experimental animals in the "open field" test (Lieshchova et al, 2018(Lieshchova et al, , 2023bBrygadyrenko et al, 2019;Lieshchova & Brygadyrenko, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of the literature sources revealed that over recent decades, drugs made from S. marianum have been successfully used to treat patients with liver pathologies, both animals and humans. Experimental in vitro and in vivo studies exhibited strong hepatoprotectory effect of S. marianum as a fodder or a supplement to fodder for agricultural animals and poultry (Khaleghipour et al, 2019;Gutyj et al, 2022;Tedesco & Guerrini, 2022;Lieshchova & Brygadyrenko, 2023). Hepatoprotectors are important means for treating animals and humans with liver pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the comparative safety of many species of spice plants used to protect the health of living organisms (Panickar, 2013), many of them are capable of exerting a negative influence on the human organism and the organisms of model animals (Jacques & Bradatan, 2021;Koss-Mikołajczyk et al, 2021;Lietzow, 2021). Despite this, many species of plants , when added to the diet in minimum amounts, are capable of regulating the metabolism , reducing the weight of humans and animals with obesity (Wang & Zhu, 2016;Shang et al, 2021;Lieshchova & Brygadyrenko, 2023).…”
Section: Introductionmentioning
confidence: 99%